Prevalence of Ciprofloxacin Resistance among Gram-Negative Bacilli Isolated From Urinary Tract Infection Specimens at a Specialist Hospital in Riyadh, Saudi Arabia - Hossain, Md. Afzal; Mohal, Shirin; Islam, Md. Saiful; Yusuf, Mohammad Abdullah (Journal of Science Foundation, 2013)
Background: Susceptibility to fluoroquinolones is very important information before prescribing to the urinary tract infection (UTI) patients. Objective: The purpose of the present study was to see the sensitivity pattern of the Gram-Negative bacilli isolated from urinary tract infection to various antibiotics as well as to know the prevalence rate of Ciprofloxacin resistance. Methodology: This cross sectional study was conducted in a specialized hospital in Riyadh, Saudi Arabia from January2006 to June2006 for over a period of six months. The Gram-negative bacilli (GNB) were isolated from clinical specimens of UTIs and antibiotic susceptibility testing was performed. Isolates with resistance or with a decreased susceptibility to Ciprofloxacin (20 mm) were than screened for their minimum inhibitory concentration (MIC) by using the E-test. Results: Out of 510 GNB, 97(19%) isolates were resistant to Ciprofloxacin. The MIC of these isolates ranged from 4 to 32µg/ml. Most of the Ciprofloxacin resistant isolates were from urinary tract infections (UTI) of hospital patients both (indoor & outdoor). The Ciprofloxacin resistance was also closely associated with multi-drug resistance, thus limiting the treatment options. Conclusion: The considerably high MIC values for Ciprofloxacin in this study reflected the extent of the treatment problems for these resistant isolates. DOI: http://dx.doi.org/10.3329/jsf.v11i1.19395